Radiation shielding lead-free glass based on barium-bearing glass using Thailand Quartz sands - Won-In K. (2014)
Lead glass that shows a high refractive index is the best known and most popular for radiation shielding glass. Due to the toxic of lead compounds on the human organisms as well as the environmental issues, lead free glass was fabricated by using some heavy elements such as barium and bismuth to replace lead. In this study, colorless lead free glass samples were prepared from 40 wt% local quartz sand and various concentration of BaCO3 (20-40 wt%) as the main compositions in order to study radiation shielding property. The glass mixtures were melted conventionally using electric furnace at the maximum temperature of 1250°C with 4 hr dwelling time. The gamma attenuation characteristics were studied for the photon energy of 662 keV from Cs-137. Density and refractive index were also determined. It was found that a variation of prepared glass samples can be produced both in terms of clarity and radiation shielding properties. The attenuation coefficients were linearly increased as the increase of BaCO3 content. The density and refractive index were also increased. The linear and mass attenuation coefficients of the glass sample containing 40 wt% BaCO3 were 0.234 cm-1 and 0.0726 cm2g-1. In conclusion, a low density glass samples will give rise less attenuation than a high density ones. It can be concluded that the lead-free high refractive index glass that is one of the environmental materials can be used as the gamma radiation shielding glass. © (2011) Trans Tech Publications.